JOB ENRICHMENT AND ORGANIZATIONAL PERFORMANCE IN SMEs IN RIVERS STATE - Nwakaego Chukuigwe (BW Academic Journal, 2022)
This work sought to examine the extent to which job enrichment enhance organizational productivity in SMEs in P/H. The study was used was built on the Mc Gregor X and Y Theory and the Herzberg Two factor Theory. The study found that job enrichment can affect organizational productivity. The study finally made some recommendations that: employees should be involved in decision making so as to give them a sense of belonging; employers should embark on motivational activities as to promote commitment to work among employees and that training and re-training programs should be carried out for the benefit of the employee so their self actualization can be achieved.